DEVELOPING INFORMATION TECHNOLOGY-BASED TOURISM: STUDY ON A TOURIST VILLAGE - Ketut Nama; Ambar Pujiharjanto; Budi Santosa (FEB Universitas Sultan Ageng Tirtayasa, 2021)
Advances in information technology demand adaptation in all aspects of life, including the tourism sector. The development of technology-based tourism must align with the increasingly massive use of social media, internet and the emergence of a cashless society. This study aims to analyze the factors that influence tourists' perceptions of the development of technology-based tourism and the determinants of tourists' decisions to revisit tourist destinations, with the OLS and Logistic Model. The regression analysis shows that the increasing use of social media, cashless habits, and the younger age are prefer to develop technology-based tourism. Tourists will revisit the destination if the tourist attraction and satisfaction level are more reliable.